Natural Cholinesterase activity in some local animals: Review (NTU Journal of Agriculture and Veterinary Science, 2025)
Organophosphorus are among the common causes of poisoning when used as a pesticide due to its easy access to local markets and its cheap price. Because of their wide and rapid effect, citizens purchase them. The instructions for use are not adhered to due to the lack of awareness among the user, which causes the surrounding environment of animals and birds to be exposed to poisoning with these insecticides through contact or contamination of their food and water, causing the inhibition of the activity of cholinesterase, which is one of the  important enzymes in the body of living organisms (ChE) and is irreversible, causing the neurotransmitter acetylcholine to accumulate in the nerve endings and sites of muscle attachment to the nerves, causing signs of poisoning, which are muscarinic and nicotinic signs, In addition to affecting the central nervous system. The current study aims to present the normal values of the cholinesterase enzyme in some field animals, the activity of which was measured by a simple electrometric method to measure blood samples (Plasma and RBC) in the animals. It cited literature related to the normal activities of the choline enzyme in a number of animals, which includes (Cows, sheep, buffalo, goats, dogs and cats, The cholinesterase enzyme (ChE) activity was measured by electrometric method. The electrometric method was effective, Simple, accurate and reproducible to detect exposure of animals in the natural environment to organophosphate or carbamate pesticides as an indicator of environmental pollution.